The climate-economic model of 27 EU countries at the NUTS 3 level - Hadačová, Daniela; Jusková, Dominika; Maličká, Lenka; Vancová, Jana (Frontiers in Environmental Science, 2025)
This paper examines the relationship between the changes in air temperature over recent decades and the economic performance of the European Union (EU) countries. It provides the climate-economic model of EU countries, considering the NUTS 3 regions to capture the within-country differences in air temperatures and economic growth at the regional level because of evident differences in the geographical landscape—elevation and climate. The sample covers 1,200 units at the NUTS 3 level from 2000 to 2022, using a panel data approach. In addition to the analysis provided at the NUTS 3 level, the paper’s uniqueness also lies in focusing on temperature variations using the Cooling index, a weather-based technical measure designed to describe the need for air cooling (or air conditioning). The findings confirm an inverse relationship between air temperatures and economic performance. These results contribute to the climate-economic literature that provides policy implications to shape public policies dealing with the impacts and risks of climate change.